UV curable resin-linear polysiloxane hot melt composition

By using a hot melt composition based on TAr-D, combined with UV acrylate-ene curing technology, the problems of high temperature or long-term curing in the existing hot melt sealant technology are solved, and the low temperature rapid curing is achieved, avoiding damage to temperature-sensitive materials and undesired odor and yellowing problems.

CN119866355AActive Publication Date: 2025-04-22DOW SILICONES CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380064458.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-21
Filing Date
2023-09-07
Publication Date
2025-04-22
Estimated Expiration
2043-09-07

AI Technical Summary

Technical Problem

Existing hot melt sealant technologies require high temperatures or long time during the curing process, which cannot meet the protection needs of temperature-sensitive materials, and thiol-based reactants may produce undesirable odors and yellowing problems.

Method used

Using a hot melt composition based on TAr-D resin-linear block copolymer and crosslinking agent, the UV acrylate-ene curing technology can achieve rapid curing at a temperature below 60°C, avoiding the use of thiol.

Benefits of technology

The curing is achieved at low temperatures and in a short time, avoiding damage to temperature-sensitive materials, while avoiding undesired odors and yellowing problems, and improving manufacturing efficiency and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005301228240000021
    Figure BDA0005301228240000021
  • Figure BDA0005301228240000071
    Figure BDA0005301228240000071
  • Figure BDA0005301228240000131
    Figure BDA0005301228240000131
Patent Text Reader

Abstract

A hot melt composition containing: (a) a TAR-D-based resin-linear block copolymer in which a TAr siloxane unit block is linked to a D-type siloxane unit block by means of a bond comprising, in at least some cases, an alkenyl group, and (b) a TAR-D-based resin-linear block copolymer in which a TAR siloxane unit block is linked to a D-type siloxane unit block by means of a bond comprising, in at least some cases, an alkenyl group; with the proviso that the concentration of such alkenyl groups is in the range of 0.5 mol% to 3.0 mol% with respect to the total number of moles of silicon atoms in the resin-linear block copolymer; (b) a cross-linking agent containing on average at least two (meth) acryloyloxy groups per molecule; (c) a free radical photoinitiator; and optionally (d) an ultraviolet stabilizer; and optionally (e) an adhesion promoter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to ultraviolet light curable silicone hot melt compositions, methods for curing such compositions and articles containing such compositions. Background Art

[0002] The market for mini and micro light-emitting diodes (LEDs) is growing rapidly, in part due to use in displays and automotive applications. Mini LED arrays can be used as backlight panels for standard LCDs and improve brightness, contrast, and black levels. Micro LEDs refer to tiny LEDs used directly as display pixels, specifically combining red, green, and blue LED dots. Both technologies require encapsulants to protect the fragile LEDs and improve light extraction by replacing air with a silicone interlayer.

[0003] The encapsulation composition has historically been applied to the LED assembly by a liquid injection method. Recently, hot melt systems have found to be more popular due to their advantages over liquid injection systems. Such advantages include ease of covering large areas, process simplicity, and reworkability.

[0004] One form of sealant technology is the use of a silicone sealant material that is cured by hydrosilylation after application to the LED assembly. Hydrosilylation typically requires elevated temperatures, typically in excess of 60 degrees Celsius (°C) and / or a cure time of one hour or more. Unfortunately, some display designs incorporate temperature sensitive materials that cannot be exposed to elevated temperatures without compromising their functionality. Therefore, in order to protect temperature sensitive materials and improve manufacturing efficiency to meet the growing demand for mini and micro LED devices, it is desirable to identify a hot melt encapsulation technology that does not require the temperatures or times of hydrosilylation curing systems.

[0005] WO2017068762 discloses a hot melt ultraviolet (UV) curable system using thiol-ene chemistry. Although this system can be cured at lower temperatures than hydrosilylation curing systems, these hydrosilylation curing systems use thiol-based reactants, which may produce undesirable odors and may cause yellowing.

[0006] It would advance the LED encapsulant art to identify a hot melt encapsulant composition that cures at temperatures below 60°C and / or has a cure time of one hour or less, or even 30 minutes or less, and that also does not use thiol-based reactants. Summary of the invention

[0007] The present invention provides a hot melt sealant composition that cures at temperatures below 60°C and / or has a cure time of one hour or less, or even 30 minutes or less, and also without the use of thiol-based reactants.

[0008] The present invention arises from the discovery of a resin-linear technology that can undergo acrylate-ene UV curing and can be a suitable hot melt sealant composition without the need for unbound nanophase particles of MQ resin. The present invention utilizes T-based polymers with alkenyl functional groups. Ar -D resin-linear block copolymers are combined with a cross-linker having multiple (meth)acryloyloxy groups per molecule to provide a hot melt composition that can undergo UV acrylate-ene curing at temperatures below 60°C, even 40°C or lower, 30°C or lower, even 25°C or lower in only a few minutes, even less than a minute, without the need for any thiol component.

[0009] In a first aspect, the present invention is a hot melt composition comprising: (a) 80 to 99 parts by weight of at least one T-based Ar -D resin-linear block copolymer, the at least one based on T Ar -D resin-linear block copolymer comprising T Ar T-type siloxane unit blocks and D-type siloxane unit blocks, wherein: (i) T Ar The A-type siloxane unit blocks are connected to the D-type siloxane unit blocks through bonds selected from those having the following structure (I):

[0010]

[0011] Where Ar is C6-C 20 Aryl; R 1 Selected from C1-C 20 Alkyl groups and C2-C 20 alkenyl groups, provided that the total number of moles of silicon atoms is based on T Ar -D resin-linear block copolymer of olefinic group R 1 The average concentration of the group is in the range of 0.5 mol % to 3.0 mol %; and R 2 and R 3 Independently C1-C 20 Hydrocarbyl, each dashed line corresponds to a valence bond to a silicon, hydrogen or hydrocarbyl group; and wherein: (ii) T ArThe molar ratio of the T-type siloxane unit block to the D-type siloxane unit block is at least 2; (iii) the resin-linear block copolymer contains 8 mol% to 35 mol% of Si-OR' bonds, wherein R' is H or a C1-C8 hydrocarbon group, relative to the molar number of silicone atoms; (iv) each D-type siloxane unit block contains an average of 20 to 200 D-type siloxane units; and (v) each T-type siloxane unit block contains an average of 20 to 200 D-type siloxane units. Ar The invention relates to an adhesive composition comprising: (a) an adhesive agent having a siloxane unit block having a weight average molecular weight in the range of 500 g / mol to 10,000 g / mol; (b) 0.5 to 20 parts by mass of a cross-linking agent, the cross-linking agent containing an average of at least two (meth)acryloyloxy groups per molecule; (c) 0.1 to 10 parts by mass of a free radical photoinitiator; (d) zero to 2.0 parts by mass of a UV stabilizer; and (e) zero to 2.0 parts by mass of an adhesion promoter.

[0012] In a second aspect, the present invention is a method comprising the steps of: heating the hot melt composition of the first aspect to soften the hot melt composition, and then applying the softened hot melt composition over at least a portion of a substrate to form a coating of the hot melt composition over at least a portion of the surface of the substrate.

[0013] In a third aspect, the present invention is an article comprising the hot melt composition of the first aspect coating at least a portion of a substrate surface.

[0014] The composition of the present invention can be used as an LED encapsulant. DETAILED DESCRIPTION

[0015] When a test method number is not used to indicate a date, the test method refers to the most current test method as of the priority date of this document. Reference to a test method includes reference to both the testing association and the test method number. The following test method abbreviations and identifiers apply herein: ASTM refers to the American Society for Testing and Materials; EN refers to European Standards; DIN refers to the German Institute for Standardization; JIS refers to Japanese Industrial Standards, and ISO refers to the International Standards Organization.

[0016] Products identified by their trade names refer to compositions available under those trade names on the priority date of this document.

[0017] "Plurality" means two or more. "And / or" means "and, or as an alternative". All ranges are inclusive unless otherwise indicated. Identification of a material by a trademark or trade name means that the material has the composition sold under that trademark or trade name on the priority date of this document.

[0018] "Parts by mass" refers to the mass of a component in a composition, measured in the same measurement units as the parts by mass of other components, to provide an indication of the mass of each component relative to the mass of the other components in the composition. For example, a composition comprising 5 grams of component A and 10 grams of component B would have one part by mass of component A and two parts by mass of component B, or, alternatively, 5 parts by mass of component A and 10 parts by mass of component B. As used herein, parts by mass refers to the concentration of a component in a hot melt composition relative to the parts by mass of other components in the hot melt composition - meaning that all parts by mass are based on the same mass units of the components of the hot melt composition.

[0019] The general term "C x-y ”, “C x -C y ”, “Cx to Cy” and “Cx-Cy” are interchangeable in the context of chemical structures and refer to having x to y carbon atoms in the chemical structure.

[0020] The number average molecular weight (Mn), weight average molecular weight (Mw), polydispersity index (PDI) and free resin % values ​​of the material were determined by gel permeation chromatography (GPC) using the following method: Sample preparation: The sample was prepared in a toluene eluent with a concentration of 20 mg / mL polymer. The solution was shaken on a flatbed shaker at ambient temperature for about 2 hours. The solution was filtered through a 0.45umPTFE syringe filter before injection. GPC was performed on a Viscotek GPC Max pump and an autosampler. The flow rate was set to 1 mL / min, and the injection volume of the standard was set to 100 microliters, and the injection volume of the study sample was set to 200uL. Each sample was injected in duplicate. Separation was performed on 2 Agilent Plgel Mixed-B columns maintained at 35°C. The detector was a Viscotek TDA 305 triple detector array maintained at 35°C. The triple detector included RI, UV, LALS, RALS and DP. Software and data processing: Malvern OMNISEC 5.02 was used for data collection, and Malvern OMNISEC 5.12 was used for data reduction. Conventional molecular weight calibration was performed using a total of 17 PS linear narrow molecular weight standards with Mp values ​​ranging from 4,000 kg / mol to 0.58 kg / mol from Agilent. Calibration curve fitting was performed using a 3rd order polynomial. Therefore, all molecular weight averages, distributions, and molecular weight references provided in this report are polystyrene (PS) equivalent values, and only RI is used for molecular weight calculations.

[0021] In one aspect, the present invention is a hot melt composition. A "hot melt" composition is characterized by a softening point of 50 degrees Celsius (°C) or higher, while typically 150°C or lower. The hot melt composition of the present invention desirably has a softening point of 50°C or higher, preferably 60°C or higher, 70°C or higher, 80°C or higher, 90°C or higher, and may be 100°C or higher, while desirably 150°C or lower, preferably 125°C or lower, even 100°C or lower. The softening point of the composition is determined by the ring and ball method of JIS K6863-1994. The softening of the hot melt composition is reversible, which means that the hot melt composition can be repeatedly heated above its softening point and cooled below its softening point while maintaining hot melt behavior.

[0022] Desirably, the hot melt composition of the present invention has a storage modulus greater than 0.01 megapascal (MPa) at 25°C and a tan delta at 25°C of less than 2.0 or preferably 1.5 or less, meaning that the hot melt composition is non-flowable at 25°C. It is also desirable that the hot melt composition of the present invention have any combination of one or more of the following additional properties that make it particularly suitable as an LED encapsulant: (i) the ratio of the viscosity at 25°C divided by the viscosity at 100°C (measured in kilopascals) is 20 or greater, preferably 100 or greater, while typically 10,000 or less, and can be 5000 or less, 4000 or less, or even 3800 or less; (ii) the storage modulus at 25°C is preferably greater than 0.1 MPa, while typically 100 MPa or less, or even 50 MPa or less, 25 MPa or less, 10 MPa or less, or even 8.5 MPa or less, or 8 MPa or less; and (iii) the Tan δ value at 25°C is preferably 2.0 or less, while typically 0.01 or greater, and can be 0.05 or greater, 0.10 or greater, or even 0.12 or greater. The composition viscosity, storage modulus and Tan delta value were determined by rotational rheometry using an ARES-G2 apparatus from TA Instruments with 25 mm parallel plates and one mm sample thickness. The sample in the test apparatus was equilibrated at 20° C. for 5 minutes, and then the temperature was raised to 120° C. at a rate of 3° C. min, with data collected every 9 seconds.

[0023] The hot melt composition comprises: (a) a Ar -D resin-linear block copolymer; (b) a crosslinking agent; (c) a free radical photoinitiator; optionally (d) a UV stabilizer; and optionally (e) an adhesion promoter. The hot melt composition may and desirably does not contain a mercapto-functional siloxane. The hot melt composition even more desirably does not contain any mercapto-functional components. The hot melt may additionally or alternatively contain unbound Q-based resin particles. "Unbound" means that it does not contain particles of a T-based resin. Ar-D resin-linear block copolymer or covalent bond of crosslinking agent. "Q-based resin particles" refers to particles composed of more than 40 mol%, usually more than 50 mol%, SiO 42 Polysiloxane particles composed of siloxane units, wherein O 4 / 2 Refers to four oxygen atoms, each of which is bonded to a silicon atom and shared with another silicon atom to form a siloxane bond.

[0024] "Resin-linear block copolymer" refers to a block copolymer comprising one or more linear polymer blocks combined with one or more resin polymer blocks. "Block" refers to a repeating segment of multiple units of the same basic type. Based on T Ar -D resin-linear block copolymer including T Ar T-type siloxane unit blocks and D-type siloxane unit blocks, these T Ar The A-type siloxane unit blocks are resin polymer blocks, and these D-type siloxane unit blocks are block or linear polymers.

[0025] T Ar The siloxane unit has the chemical formula:

[0026] ArSi(OR') t O (3-t) / 2

[0027] in:

[0028] Ar refers to an aryl group having 6 or more, and may have 7 or more, 8 or more, 9 or more, 10 or more, 12 or more, 14 or more, 16 or more, even 18 or more, while typically having 20 or less, and may have 18 or less, 16 or less, 14 or less, 12 or less, 10 or less, 8 or less carbon atoms, while preferably the aryl group is a phenyl group;

[0029] R' is independently selected at each occurrence from hydrogen and hydrocarbyl groups, wherein these hydrocarbyl groups preferably have one or more, and may have 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, even 7 or more, while typically having 8 or fewer, and may have 7 or fewer, 6 or fewer, 5 or fewer, 4 or fewer, 3 or fewer, even 2 or fewer carbon atoms;

[0030] The subscript t is the number of (OR') groups attached to the silicon atom and generally has a value in the range of zero to 2; and

[0031] O (3-t) / 2Refers to a (3-t) oxygen atom that is bonded to a silicon atom and shared with another silicon atom to form a siloxane bond.

[0032] T Ar The block of T-type siloxane units contains multiple T-type siloxane units held together by shared siloxane bonds. Ar Type siloxane unit.

[0033] The D-type siloxane unit has the general chemical formula: R2SiO 2 / 2 ; Among them O 2 / 2 Refers to two oxygen atoms bonded to a silicon atom and shared with another silicon atom to form a siloxane bond; and each R is independently selected from a hydrocarbon group having one or more, and may have 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, even 7 or more, 8 or more, 10 or more, 12 or more, 14 or more, 16 or more, even 18 or more, while typically having 20 or less, 18 or less, 16 or less, 14 or less, 12 or less, 10 or less, 8 or less, and may have 7 or less, 6 or less, 5 or less, 4 or less, 3 or less, even 2 or less carbon atoms. Typically, each R group is methyl. The block of D-type siloxane units comprises a plurality of D-type siloxane units bonded together by shared siloxane bonds.

[0034] Based on T Ar The resin-linear block copolymers of -D are also characterized by the following properties:

[0035] (i)T Ar The D-type siloxane block is bonded to the D-type silicon via a bond selected from those having the following structure (I)

[0036] Oxyalkylene unit block connection:

[0037]

[0038] Wherein: Ar is as described above; R 1 Selected from C1-C 20 Alkyl groups and C2-C 20 an alkenyl group (preferably a vinyl group), provided that based on T Ar -D resin-linear block copolymer R 1The average concentration of the alkenyl groups is in the range of 0.5 mol% to 3.0 mol% (mol%), and can be 0.5 mol% or more, 0.75 mol% or more, 1.0 mol% or more, 1.5 mol% or more, 2.0 mol% or more, or even 2.5 mol% or more, and 3.0 mol% or less, and can be 2.5 mol% or less, 2.0 mol% or less, 1.5 mol% or less, or even 1.0 mol% or less, relative to the total moles of silicon atoms; and R 2 and R 3 are independently selected from R groups as described above, and are preferably selected from methyl groups and ethyl groups; and each dotted line corresponds to a valence bond to silicon, hydrogen or a hydrocarbyl group;

[0039] (ii)T Ar The molar ratio of the D-type siloxane unit block to the D-type siloxane unit block is 2 or more, and preferably each D-type siloxane unit is connected at either end by a T Ar Type siloxane unit block end-capping;

[0040] (iii) Compared with the T-based Ar -D The total number of moles of silicone atoms in the resin-linear block copolymer, based on T Ar -D has sufficient OR' groups to provide 8 or more, and possibly 9 or more, 10 or more, 11 or more, 12 or more, 14 or more, 16 or more, 18 or more, 20 or more, 22 or more, 24 or more, 26 or more, even 28 or more, and 35 or less, and possibly 30 or less, 25 or less, 20 or less, 15 or less, even 10 or less mole percent (mol %) Si-OR' bonds; and

[0041] (iv) each D-type siloxane unit block contains an average of 10 to 200 D-type siloxane units, and may contain an average of 10 or more, 20 or more, 30 or more, 40 or more, 50 or more, 60 or more, 70 or more, 80 or more, 90 or more, 100 or more, 120 or more, 140 or more, 160 or more, or even 180 or more, while typically containing 200 or less, 180 or less, 160 or less, 140 or less, 120 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, or even 20 or less D-type siloxane units; and

[0042] (v) Each T Ar The type siloxane unit block has a weight average molecular weight (Mw) in the range of 500 g / mole to 10,000 g / mole, and may have an Mw of 500 or more, 750 or more, 1000 or more, 2500 or more, 5000 or more, or even 7500 or more, while typically being 10,000 or less, 7500 or less, 5000 or less, 2500 or less, and may be 1000 or less, or even 750 or less.

[0043] pass 29 Si NMR spectroscopy based on T Ar The average number of D-type siloxane units in the resin-linear block copolymer of T-D was determined by gel permeation chromatography (GPC) using the procedure described above. Ar -D resin-linear block copolymer T Ar The average Mw of the siloxane unit block.

[0044] Based on T Ar The resin-linear block copolymer of -D may be free of (meth)acryloyloxy groups. In fact, the entire composition may be free of (meth)acyloxy-functional polysiloxanes.

[0045] The hot melt composition comprises 80 parts by mass or more, and may comprise 85 parts by mass or more, 90 parts by mass or more, 95 parts by mass or more, or even 97 parts by mass or more, and generally comprises 99 parts by mass or less, and may comprise 98 parts by mass or less, 95 parts by mass or less, 90 parts by mass or less, or even 85 parts by mass or less of at least one T-based Ar -D resin - linear block copolymer.

[0046] Based on T Ar The resin-linear block copolymer of -D may not contain olefinic functional R"3SiO 1 / 2 Siloxane units, wherein R" is a hydrocarbon group, and O 1 / 2 Refers to the oxygen that is bonded to a silicon atom and shared with another silicon atom in a siloxane bond.

[0047] The crosslinking agent is a molecule containing an average of two or more (meth)acryloyloxy groups per molecule, and may contain 3 or more, or even 4 or more, while typically containing 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, or even 3 or less (meth)acryloyloxy groups per molecule.

[0048] In order to avoid loss of composition components during heating (i.e., in order to obtain stable curability), it is desirable that the crosslinking agent and / or free radical photoinitiator have a boiling point above 100°C, preferably 150°C or higher, more preferably 200°C or higher, and typically 400°C or lower, and may be 350°C or lower, 300°C or lower, 250°C or lower, or even 200°C or lower at a pressure of 101 kPa.

[0049] The cross-linking agent may be one or more than one compound selected from compounds having the average chemical structures (III) and (IV):

[0050] R' m CX (4-m) (III)

[0051] XR”-X (IV)

[0052] in:

[0053] each R' is independently selected at each occurrence from an alkyl group having from one to 20 carbon atoms, and can have one or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 10 or more, 12 or more, 14 or more, 16 or more, or even 18 or more, while typically having 20 or less, 18 or less, 16 or less, 14 or less, 12 or less, 10 or less, 8 or less, 6 or less, 4 or less, or even 2 or less carbon atoms;

[0054] Each X is independently selected from -CH2OC(O)CH=CH2 and -CH2OC(O)C(CH3)=CH2 groups, and

[0055] R" is an alkylene group having from one to 20 carbon atoms, and can have one or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, 10 or more, 11 or more, 12 or more, 14 or more, 16 or more, or even 18 or more, while 20 or less, 18 or less, 16 or less, 14 or less, 12 or less, 10 or less, 8 or less, 6 or less, 4 or less, or even 2 or less carbon atoms.

[0056] Examples of suitable crosslinking agents include trimethylolpropane triacrylate, pentaerythritol tetraacrylate, and 1,12-dodecanediol dimethacrylate.

[0057] The concentration of the crosslinking agent in the hot melt composition is generally in the range of 0.5 parts by mass to 20 parts by mass, and may be present in a concentration of 0.5 or more, 1.0 or more, 2.0 or more, 4.0 or more, 6.0 or more, 8.0 or more, 10.0 or more, 12.0 or more, 14.0 or more, 16.0 or more, and even 18.0 or more, while typically 20.0 or less, 18.0 or less, 16.0 or less, 14.0 or less, 12.0 or less, 10.0 or less, 8.0 or less, 5.0 or less, 4.0 or less, 3.0 or less, 2.0 or less, and even 1.0 or less parts by mass.

[0058] The hot melt composition comprises a free radical photoinitiator in a concentration of 0.1 parts by mass or more, 0.5 parts by mass or more, 1.0 parts by mass or more, 2.0 parts by mass or more, 3.0 parts by mass or more, 4.0 parts by mass or more, 5.0 parts by mass or more, 6.0 parts by mass or more, 7.0 parts by mass or more, 8.0 parts by mass or more, and even 9.0 parts by mass or more, while 10 parts by mass or less, 9.0 parts by mass or less, 8.0 parts by mass or less, 7.0 parts by mass or less, 6.0 parts by mass or less, 5.0 parts by mass or less, 4.0 parts by mass or less, 3.0 parts by mass or less, 2.0 parts by mass or less, and even 1.0 parts by mass or less.

[0059] The free radical photoinitiator can be, for example, any one or a combination of more than one components selected from the group consisting of benzophenone and benzophenone derivatives, acetophenone and acetophenone derivatives, benzoin and its alkyl esters, phosphine oxide derivatives, xanthone derivatives, oxime ester derivatives and camphorquinone. Suitable commercially available photoinitiators include any one or any combination of more than one selected from the following: 2,6-bis(4-azidobenzylidene)cyclohexanone; 2,6-bis(4-azidobenzylidene)-4-methylcyclohexanone; 1-hydroxy-cyclohexyl-phenyl-ketone (known under the name OMNIRAD TM184); 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one (obtained under the name OMNIRAD 907); 2-hydroxy-2-methyl-1-phenyl-propan-1-one (obtained under the name OMNIRAD 1173); 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone (obtained under the name OMNIRAD 2959); methyl benzoylformate (obtained under the name OMNIRAD MBF); α,α-dimethoxy-α-phenylacetophenone (obtained under the name OMNIRAD 651); 2-benzyl-2-(dimethylamino)-1-[4-(4-morpholino)phenyl]-1-butanone (obtained under the name OMNIRAD 369); diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (available under the name OMNIRADTPO); ethyl (2,4,6-trimethylbenzoyl)phenylphosphinate (available under the name OMNIRAD TPO-L); oxime ester compounds (available as products N-1919, NCI-831, NCI-930, NCI-730 and NCI-100 from Adeka Corporation), 12-thioxanthen-9-one; 10-methylphenothiazine; isopropyl-9H-thioxanthen-9-one; 2,4-diethyl-9H-thioxanthen-9-one; 2-chlorothioxanthen-9-one; and 1-chloro-4-propoxy-9H-thioxanthen-9-one. OMNIRAD is a trademark of IGM Group BV. One particularly desirable free radical photoinitiator is 2,4,6-trimethylbenzoyl-phenylphosphinate.

[0060] Optionally, the hot melt composition may include a UV stabilizer. UV stabilizers are free radical scavengers, and these UV stabilizers can extend the storage stability of the hot melt composition by inhibiting curing until the hot melt composition is intentionally exposed to UV light. UV stabilizers include phenolic compounds, such as any one of the following or any combination of more than one: 4-methoxyphenol (MEHQ, methyl ether of hydroquinone), hydroquinone, 2-methylhydroquinone, 2-tert-butylhydroquinone, tert-butylcatechol, butylated hydroxytoluene and butylated hydroxyanisole. Other types of UV stabilizers include phenothiazines and anaerobic inhibitors, such as NPAL type inhibitors (tris-(N-nitroso-N-phenylhydroxylamine) aluminum salts) available from Albemarle Corporation.

[0061] The concentration of the UV stabilizer is typically zero parts by mass or more, and may be 0.1 parts by mass or more, 0.5 parts by mass or more, 1.0 parts by mass or more, or even 1.5 parts by mass or more, and is typically 2.0 parts by mass or less, 1.5 parts by mass or less, 1.0 parts by mass or less, or even 0.5 parts by mass or less.

[0062] Optionally, the hot melt composition may contain an adhesion promoter. Suitable adhesion promoters include organosilicon compounds having at least one silicon-bonded alkoxy group in the molecule. The alkoxy group is exemplified by a methoxy group, an ethoxy group, a propoxy group, a butoxy group, and a methoxyethoxy group, wherein the methoxy group is particularly preferred. In addition, the silicon-bonded groups other than the alkoxy groups in the organosilicon compound are exemplified by halogen-substituted or unsubstituted monovalent hydrocarbon groups such as alkyl groups, alkenyl groups, aryl groups, aralkyl groups, halogenated alkyl groups, halogenated aryl groups, and halogenated aralkyl groups; glycidyloxyalkyl groups such as 3-glycidyloxypropyl groups and 4-glycidyloxybutyl groups; epoxycyclohexylalkyl groups such as 2-(3.4-epoxycyclohexyl)ethyl groups and 3-(3.4-epoxycyclohexyl)propyl groups; epoxyalkyl groups such as 3,4-epoxybutyl groups and 7,8-epoxyoctyl groups; monovalent organic groups containing acrylic groups such as 3-methacryloyloxypropyl groups; and hydrogen atoms. The adhesion promoter preferably contains a group that can react with an alkenyl group or a silicon-bonded hydrogen atom. Specifically, the adhesion promoter preferably contains silicon-bonded hydrogen atoms or alkenyl groups. In addition, since it is possible to impart good adhesion to various types of substrates, the adhesion promoter preferably has at least one monovalent organic group containing an epoxy group in the molecule. Examples of this type of adhesion promoter are organosilane compounds, organosiloxane oligomers, and alkyl silicates. Examples of the molecular structure of organosiloxane oligomers or alkyl silicates are straight chain, partially branched straight chain, branched chain, cyclic, and network structures. Straight chain, branched chain, and network structures are particularly preferred. Examples of adhesion promoters are silane compounds such as 3-glycidoxypropyltrimethoxysilane, 2-(3.4-epoxycyclohexyl)ethyltrimethoxysilane, and 3-methacryloxypropyltrimethoxysilane; siloxane compounds having at least one silicon-bonded alkenyl group or each of a silicon-bonded hydrogen atom and a silicon-bonded alkoxy group in the molecule; a mixture of a silane compound having at least one silicon-bonded alkoxy group or a siloxane compound and a siloxane compound having at least one silicon-bonded hydroxyl group and at least one silicon-bonded alkenyl group in the molecule; and methyl polysilicate, ethyl polysilicate, and ethyl polysilicate containing an epoxy group. The adhesion promoter is preferably a low-viscosity liquid, and the viscosity of the adhesion promoter is not particularly limited, but is preferably 1 mPa-500 millipascals (mPa) at 25°C.

[0063] The concentration of the adhesion promoter is typically zero parts by mass or higher, and can be 0.1 parts by mass or higher, 0.5 parts by mass or higher, 1.0 parts by mass or higher, or even 1.5 parts by mass or higher, while typically being 2.0 parts by mass or lower, 1.5 parts by mass or lower, 1.0 parts by mass or lower, or even 0.5 parts by mass or lower.

[0064] It is noteworthy that the hot melt composition of the present invention can be free of hydrosilylation catalysts, such as platinum catalysts. Therefore, the hot melt composition can be free of platinum, which is desirable to avoid yellowing of the composition and keep costs lower than systems requiring platinum catalysts.

[0065] In another aspect, the present invention is a method for using the hot melt composition of the present invention as a curable coating on a substrate. The method comprises the steps of heating the hot melt composition according to the present invention to soften the hot melt composition, and then applying the softened hot melt composition over at least a portion of a substrate to form a coating of the hot melt composition over at least a portion of the substrate surface. The method also comprises exposing the coating of the hot melt composition to ultraviolet light to cause crosslinking of the composition coating. When the (meth)acryloyloxy groups of the crosslinking agent are bonded to the T-based Ar -D When the alkenyl groups of the resin-linear block copolymer react, crosslinking occurs.

[0066] In a particularly desirable application, the hot melt composition of the present invention is an encapsulant for light emitting diodes. In such applications, the method is as described above, and the substrate on which the hot melt composition is coated includes light emitting diodes. The coating covers the light emitting diodes, thereby encapsulating these light emitting diodes, and then the coating is cured by exposure to UV light.

[0067] In yet another aspect, the invention is an article comprising the hot melt composition of the invention coating at least a portion of a substrate surface. Desirably, the substrate, and most desirably the portion of the substrate coated with the hot melt composition, comprises a light emitting diode.

[0068] Example

[0069] Synthesis of silanol terminated polydimethylsiloxane (PDMS)

[0070] The silanol-terminated PDMS materials used in the following examples were prepared by starting with a shorter chain silanol-terminated PDMS and reacting using a potassium hydroxide (KOH) catalyst solution to produce a longer chain silanol-terminated PDMS while purging the reaction with nitrogen to remove water during the reaction. The chain length was monitored by monitoring the change in OH band concentration in Fourier transform infrared spectroscopy (FT-IR). Different chain lengths can be prepared by starting with silanol-terminated PDMS of different chain lengths, using different concentrations of catalyst and by carrying out the reaction for different times. Once the reaction is complete, the reaction is carried out by 29 Si NMR confirmed the degree of polymerization (DP). The silanol terminated PDMS materials of the following examples are characterized in Table 1.

[0071] Table 1

[0072]

[0073] The following are the procedures for the longest and shortest silanol-terminated PDMS used in the examples. One of ordinary skill should be able to prepare mid-range silanol-terminated PDMS materials based on these procedures. The method uses a starting silanol-terminated PDMS with a viscosity in the range of 50 centistokes to 120 centistokes (available from The Dow Chemical Company under the name XIAMETER TM PMX-0156 is commercially available. XIAMETER is a trademark of Dow Silicones Corporation. DOWSIL is a trademark of The Dow Chemical Company.)

[0074] Silanol terminated PDMS1: degree of polymerization (DP) = 54

[0075] 500.0 g of the starting silanol-terminated PDMS was added to a one-liter 3-neck round-bottom flask equipped with a polytetrafluoroethylene stirring paddle and a thermocouple, keeping one neck open while purging with nitrogen at a flow rate of 1.5 standard cubic feet per hour. 0.17 g of a 3 wt% potassium hydroxide solution was added to the flask at 90°C. After 3 hours at 90°C, 0.53 g of a 2.5 wt% aqueous phosphoric acid solution was added. The solution was cooled to 25°C. Purge with nitrogen overnight to remove water. Filter through a nylon filter to obtain PDMS1. 29 Si NMR confirmed that PDMS1 had a DP of 54.

[0076] Silanol terminated PDMS2: DP = 98

[0077] 1255.6 g of the starting silanol-terminated PDMS was added to a one-liter 3-necked round-bottom flask equipped with a polytetrafluoroethylene stirring paddle and a thermocouple, with one neck left open while purging with nitrogen at a flow rate of 1.5 standard cubic feet per hour. 0.42 g of a 3 wt% potassium hydroxide solution was added to the flask at 90°C. The mixture was heated at 90°C for 3 hours and 1 After 2 hours, 1.32 g of 2.5 wt% phosphoric acid aqueous solution was added. The solution was cooled to 25°C. Nitrogen was purged overnight to remove water. Filtered through a nylon filter to obtain PDMS2. 29 Si NMR confirmed that PDMS2 had a DP of 98.

[0078] Based on T Ar Synthesis of D-resin-linear block copolymers RL1-RL6

[0079] In addition to PDMS1-4, Table 2 lists the components used with the silanol-terminated PDMS to prepare RL1-RL6.

[0080] Table 2

[0081]

[0082] DOWSIL is a trademark of The Dow Chemical Company.

[0083] RL1: 45wt% resin / 55wt% silanol-terminated PDMS1 and vinyl functionalized

[0084] 90.0 g of resin and 185.5 g of toluene were charged to a one liter (1 L) four-necked round bottom flask equipped with a thermocouple, a polytetrafluoroethylene stirring paddle, and a Dean Stark apparatus connected to a water-cooled condenser. Sufficient additional toluene was added to equal the volume of the Dean Stark apparatus. An inert gas blanket was applied and refluxed for 30 minutes to remove water.

[0085] Diacetoxysilane terminated PDMS was prepared by adding 8.50 g of VTA and 5.49 of acetoxysilane to a mixture of 59.2 g of toluene and 110.0 g of silanol terminated PDMS 1 in a 500 ml round bottom flask. The mixture was stirred for one hour. The resulting diacetoxysilane terminated PDMS was quickly added to the flask containing the resin at 106°C to form a reaction mixture. Refluxed for 2 hours. The reaction mixture was cooled to 90°C and 21.9 g of deionized water was added. Water and acetic acid byproduct were removed by azeotropic distillation. Water was added and removed again. 81.0 g of volatiles were removed by distillation to obtain a concentrated solution. The addition and removal of water were repeated three times. The resulting solution was filtered through a 5 micron nylon filter. The volatiles were reduced using a rotary evaporator to increase the solid content. Based on the mass of the solution, a translucent solution of RL1 in toluene retained an active concentration of RL1 of 79.6 mass %.

[0086] RL2: 35wt% resin / 65wt% silanol-terminated PDMS2 and vinyl functionalized

[0087] 70.0 g of resin and 230.0 g of toluene were charged to a one liter (1 L) four-necked round bottom flask equipped with a thermocouple, a polytetrafluoroethylene stirring paddle, and a Dean Stark apparatus connected to a water-cooled condenser. Sufficient additional toluene was added to equal the volume of the Dean Stark apparatus. An inert gas blanket was applied and refluxed for 30 minutes to remove water.

[0088] Diacetoxysilane-terminated PDMS was prepared by adding 8.50 g of VTA and 0.56 of acetoxysilane to a mixture of 70.0 g of toluene and 130.0 g of silanol-terminated PDMS 2 in a 500 ml round-bottom flask. The mixture was stirred for one hour. The resulting diacetoxysilane-terminated PDMS was quickly added to the flask containing the resin at 106°C to form a reaction mixture. Reflux for 2 hours. The reaction mixture was cooled to 106°C and 1.75 g of acetoxysilane was added. Reflux for one hour. The mixture was cooled to 25°C and 16.9 g of deionized water was added. Water and acetic acid by-products were removed by azeotropic distillation. Water was added and removed again. Volatiles were removed by distillation to obtain a concentrated solution. The addition and removal of water was repeated three times. The resulting solution was filtered through a 5 micron nylon filter. Volatiles were reduced using a rotary evaporator to increase the solid content. A translucent solution of RL2 in toluene retained an active concentration of 72.9 mass % RL2 in toluene based on the mass of the solution.

[0089] RL3: 45wt% resin / 55wt% silanol-terminated PDMS4 and vinyl functionalized

[0090] 270.0 g of resin and 722.3 g of toluene were charged to a 3 liter (3 L) four-necked round bottom flask equipped with a thermocouple, a polytetrafluoroethylene stirring paddle, and a Dean Stark apparatus connected to a water-cooled condenser. Sufficient additional toluene was added to equal the volume of the Dean Stark apparatus. An inert gas blanket was applied and refluxed for 30 minutes to remove water.

[0091] Diacetoxysilane terminated PDMS was prepared by adding 25.50 g VTA and 10.36 g acetoxysilane to a mixture of 177.7 g toluene and 330.0 g silanol terminated PDMS 4 in a 500 ml round bottom flask. The mixture was stirred for one hour. The resulting diacetoxysilane terminated PDMS was quickly added to the flask containing the resin at 106°C to form a reaction mixture. Refluxed for 2 hours. The mixture was cooled to 90°C and 56.0 g deionized water was added. Water and acetic acid byproduct were removed by azeotropic distillation. Water was added and removed again. 300.0 g volatiles were removed by distillation to obtain a concentrated solution. The addition and removal of water were repeated three times. The resulting solution was filtered through a 5 micron nylon filter. The volatiles were reduced using a rotary evaporator to increase the solids content. The translucent solution of RL3 in toluene retained an active RL3 concentration of 78.7 mass % based on the solution mass.

[0092] RL4: 45wt% resin / 55wt% silanol-terminated PDMS2 and vinyl functionalized

[0093] 90.0 g of resin and 230.0 g of toluene were charged to a one liter (1 L) four-necked round bottom flask equipped with a thermocouple, a polytetrafluoroethylene stirring paddle, and a Dean Stark apparatus connected to a water-cooled condenser. Sufficient additional toluene was added to equal the volume of the Dean Stark apparatus. An inert gas blanket was applied and refluxed for 30 minutes to remove water.

[0094] Diacetoxysilane terminated PDMS was prepared by adding 7.71 g VTA to a mixture of 70.0 g toluene and 110.0 g silanol terminated PDMS 2 in a 500 ml round bottom flask. The mixture was stirred for one hour. The resulting diacetoxysilane terminated PDMS was quickly added to the flask containing the resin at 106°C to form a reaction mixture. Reflux for 2 hours. The reaction mixture was cooled to 106°C and 0.79 g VTA and 6.72 g acetoxysilane were added. Reflux for one hour. The mixture was cooled to 90°C and 23.8 g deionized water was added. Water and acetic acid byproduct were removed by azeotropic distillation. Water was added and removed again. Volatiles were removed by distillation to obtain a concentrated solution. The addition and removal of water were repeated three times. The resulting solution was filtered through a 5 micron nylon filter. Volatiles were reduced using a rotary evaporator to increase the solids content. The translucent solution of RL4 in toluene retained an active RL4 concentration of 71.1 mass % based on the solution mass.

[0095] RL5: 45wt% resin / 55wt% silanol-terminated PDMS 3 and vinyl functionalized

[0096] 90.0 g of resin and 240.8 g of toluene were charged to a one liter (1 L) four-necked round bottom flask equipped with a thermocouple, a polytetrafluoroethylene stirring paddle, and a Dean Stark apparatus connected to a water-cooled condenser. Sufficient additional toluene was added to equal the volume of the Dean Stark apparatus. An inert gas blanket was applied and refluxed for 30 minutes to remove water.

[0097] Diacetoxysilane terminated PDMS was prepared by adding 8.50 g of VTA to a mixture of 59.2 g of toluene and 110.0 g of silanol terminated PDMS 3 in a 500 ml round bottom flask. The mixture was stirred at 25 °C for one hour. The resulting diacetoxysilane terminated PDMS was quickly added to the flask containing the resin at 106 °C to form a reaction mixture. Reflux for 2 hours. The reaction mixture was cooled to 106 °C and 7.49 g of acetoxysilane was added. Reflux for one hour. The mixture was cooled to 90 °C and 25.1 g of deionized water was added. Water and acetic acid byproduct were removed by azeotropic distillation. Water was added and removed again. 100 g of volatiles were removed by distillation to obtain a concentrated solution. The addition and removal of water were repeated three times. The resulting solution was filtered through a 5 micron nylon filter. The volatiles were reduced using a rotary evaporator to increase the solid content. The translucent solution of RL5 in toluene retained an active RL5 concentration of 78.7 mass % based on the solution mass.

[0098] RL6: 45wt% resin / 55wt% silanol-terminated PDMS 4 without olefin functionalization

[0099] 90.0 g of resin and 240.8 g of toluene were charged to a one liter (1 L) four-necked round bottom flask equipped with a thermocouple, a polytetrafluoroethylene stirring paddle, and a Dean Stark apparatus connected to a water-cooled condenser. Sufficient additional toluene was added to equal the volume of the Dean Stark apparatus. An inert gas blanket was applied and refluxed for 30 minutes to remove water.

[0100] Diacetoxysilane terminated PDMS was prepared by adding 11.78 g of acetoxysilane to a mixture of 59.3 g of toluene and 110.0 g of silanol terminated PDMS 4 in a 500 ml round bottom flask. The mixture was stirred for one hour. The resulting diacetoxysilane terminated PDMS was quickly added to the flask containing the resin at 106°C to form a reaction mixture. Refluxed for 2 hours. The solution was cooled to 25°C and 18.7 g of deionized water was added. Water and acetic acid byproduct were removed by azeotropic distillation. Water was added and removed again. Volatiles were removed by distillation to obtain a concentrated solution. The addition and removal of water were repeated three times. The resulting solution was filtered through a 5 micron nylon filter. The volatiles were reduced using a rotary evaporator to increase the solids content. The translucent solution of RL6 in toluene retained an active RL6 concentration of 73.1 mass % relative to the mass of the solution.

[0101] Table 3 presents the Ar Summary of the properties of the linear block copolymers RL1-RL6 of the resin-D.

[0102] Table 3

[0103]

[0104] Sample composition

[0105] The following sample compositions were prepared using RL1-RL6 and the components of Table 4.

[0106] Table 4

[0107]

[0108]

[0109] The samples were prepared by uniformly mixing the mass parts of each component specified in Table 5 in toluene to form the samples. The prepared solution of the resin-linear component in toluene was used for the resin-linear component in an amount corresponding to the mass parts of the active material described in Table 5 (i.e., the mass parts of the resin-linear block copolymer). The components were mixed in a dental cup and uniformly mixed using a dental mixer. The formulations were coated on ethylene tetrafluoroethylene (ETFE) films and dried at 70°C for one hour before characterization.

[0110] The dried samples were characterized to determine whether they met the requirements as "hot melt" compositions, as described above, by having a softening point in the range of 50°C-150°C, a storage modulus at 25°C greater than 0.01 MPa, a Tanδ value at 25°C less than 5.0, and a ratio of viscosity at 25°C to viscosity at 100°C greater than 20, as per JIS K6863-1994. The samples were also characterized for "curability". In order to be properly UV-curable, the samples must pass the following UV-curability test. In order to be suitable for optical encapsulants, such as LED encapsulants, the composition should cure to a material having a percent transmittance (%T) to visible light greater than 90%. %T is determined using the following procedure. [Ac] / [Vi] is the molar ratio of (meth)acryloyloxy groups to vinyl groups in the composition. The characterization results for various samples are summarized in Table 5.

[0111] UV-curability test

[0112] The sample was coated onto an ethylene tetrafluoroethylene (ETFE) film and allowed to dry at 70°C to form a 200 micron thick sample film. The sample film was covered with another ETFE film so that the sample film was sandwiched between the ETFE films. The sandwiched sample was placed in a UVitron SkyRAY with Raven variation and exposed to 365 nanometer UV radiation (250 milliwatts) for 16 seconds. The sample was flipped over and the exposure was repeated. The total UV dose was 8 joules / square centimeter of UV radiation (4 joules / square centimeter on each side).

[0113] Gel percentage

[0114] The gel percentage (Gel%) is determined by weighing a sample (approximately 1.0 g) of the cured hot melt composition to obtain the starting sample mass, placing the sample in a 40 ml dental cup, adding 15.0 g of toluene to the dental cup and shaking for one hour, decanting the toluene solution, leaving the undissolved cured hot melt material. The undissolved cured hot melt material is transferred to a tared aluminum pan, dried at 120° C. for 2 hours, and weighed to determine the mass of the undissolved cured hot melt material. Gel%=100%×(mass of undissolved cured hot melt material) / (starting sample mass).

[0115] If the UV cured sample had greater than 50% gel %, then the UV cured sample was considered suitably curable.

[0116] Optical transmittance

[0117] The %T of the cured composition was determined using a 200 micron thick film of the cured composition and a Haze-Guard Plus (BYK Gardner) using ASTM D1003.

[0118]

Claims

1. A hot melt composition, comprising: (a) 80 to 99 parts by mass of at least one T-based Ar -D resin-linear block copolymer, the at least one based on T Ar -D resin-linear block copolymer containing T Ar Type siloxane unit blocks and D-type siloxane unit blocks, wherein: (i)T Ar The A-type siloxane unit blocks are connected to the D-type siloxane unit blocks through bonds selected from those having the following structure (I): Where Ar is C6-C 20 Aryl; R 1 Selected from C1-C 20 Alkyl groups and C2-C 20 alkenyl group, provided that the total number of moles of silicon atoms is based on T Ar -D resin-linear block copolymer of olefinic group R 1 The average concentration of the group is in the range of 0.5 mol % to 3.0 mol %; and R 2 and R 3 Independently C1-C 20 Hydrocarbyl, each dashed line corresponds to a valence bond to silicon, hydrogen, or a hydrocarbyl group; And among them: (ii)T Ar The molar ratio of the A-type siloxane unit block to the D-type siloxane unit block is at least 2; (iii) the resin-linear block copolymer contains 8 mol% to 35 mol% Si-OR' bonds, relative to the moles of silicone atoms, wherein R' is H or a C1-C8 hydrocarbon group; (iv) each D-siloxane unit block contains an average of 20 to 200 D-siloxane units; and (v) Each T Ar The type siloxane unit block has a weight average molecular weight in the range of 500 g / mol to 10,000 g / mol; (b) 0.5 to 20 parts by mass of a cross-linking agent, wherein each molecule of the cross-linking agent contains an average of at least two (meth)acryloyloxy groups; (c) 0.1 to 10 parts by weight of a free radical photoinitiator; (d) zero to 2.0 parts by mass of an ultraviolet stabilizer; and (e) 0 to 2.0 parts by mass of an adhesion promoter.

2. The hot melt composition according to claim 1 or claim 2, wherein the resin-linear block copolymer does not contain a (meth)acryloyloxy group.

3. A hot melt composition according to any preceding claim, wherein Ar is phenyl, R 1 It is vinyl and R 2 and R 3 Independently selected from a methyl group and an ethyl group.

4. A hot melt composition according to any preceding claim, wherein the composition is free of unbound Q-based resin particles.

5. A hot melt composition according to any preceding claim, wherein the crosslinking agent is one or more than one compound selected from compounds having the average chemical structures (III) and (IV): R' m CX (4-m) (III) XR"-X(IV) wherein each R' at each occurrence is independently selected from an alkyl group having from one to 20 carbon atoms, each X is independently selected from -OC(O)CH=CH2 and -OC(O)C(CH3)=CH2 groups, and R" is an alkylene group having from one to 20 carbon atoms.

6. A method comprising the following steps: The hot melt composition according to any preceding claim is heated to soften the hot melt composition and then the softened hot melt composition is applied over at least a portion of a substrate to form a coating of the hot melt composition over at least a portion of the substrate surface.

7. The method of claim 7, wherein the method further comprises exposing the coating of the hot melt composition to ultraviolet light to induce crosslinking of the composition coating.

8. An article comprising the hot melt composition according to any one of claims 1 to 6 coating at least a portion of a substrate surface.

9. The article of claim 9, wherein the substrate comprises a light emitting diode.

Citation Information

Patent Citations

  • Active energy ray curable hot melt silicone composition, cured product thereof, and method of producing film

    WO2017068762A1

  • Fast ultraviolet radiation curing silicone composition

    EP0141380A2

  • Compositions of resin-linear organosiloxane block copolymers

    US20150045520A1

  • Compositions of resin-linear organosiloxane block copolymers

    US20160208055A1

  • Curable granular silicone composition and method for manufacturing thereof

    US20180105692A1